HydroTechPure Prototype Development: Dual Mode Filter-Based Water Purification Tool as a STEM-Based Learning Tool - Nahadi, Nahadi; Siswaningsih, Wiwi; Nais, Miarti Khikmatun; Rahmawati, Triannisa; Nurhadi, Atep Rian; Widiarti, Hayuni Retno; Sidiq, Ari Syahidul; Evriliani, Agnes Suci; Zahra, Aztiannisa; Sari, Liana Ambar; Razani, Ahmad Nafran; Zahran, Qurrotu Aini; Rahman, Muhammad Fiqri; Abdurrahman, Fajar (Universitas Pendidikan Mandalika, 2025)
Water is one of the most fundamental basic needs for human life. However, disparities in the availability of clean water remain a significant challenge in Indonesia. This study aims to develop a water purification device to address this issue. The research method employed was the ADDIE model, which consists of five stages, with this study focusing on analysis, design, and development, which serve as scope of this study. The result of a water purification, named HydroTechPure, utilizes a dual filter system with high quality absorbent materials and is constructed from acrylic materials, enhanced by 3D design technology and Arduino integration. The development of this device aligns with the sixth goal of the Sustainable Development Goals (SDGs), which emphasizes ensuring access to clean water and sanitation for all. HydroTechPure was developed at FabLab Edu UPI. Beyond its primary function, HydroTechPure is envisioned as a tool for integrating STEM based learning, aiming to foster students’ motivation and environmental awareness.